Resist Authoritarian Tendencies within the Party! Let a Thousand Schools of Thought Contend! - Barry, Ka (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Excerpt The very first thing that needs to be clarified about the paper "Reaffirm Our Basic Principles and Rectify Errors" by Armando Liwanag is whether the paper reflects the official position of the Central Committee (CC) of the Communist Party of the Philippines (CPP) or just the personal opinion of the author. The author has every right to speak out like everyone else, but a distinction has to be clearly made between his personal views and the position of the Party or the Party leadership as a whole.